Psychosocial correlates of alcohol intake among male adolescents in San Andres, Manila Lagrimas T. Gonzales-Moderes. - Moderes, Lagrimas T. Gonzales
Experimenting with alcohol usually occur during adolescence. Information about the factors associated with alcohol drinking among adolescents is essential in the prevention of alcohol intake which has been known to result to a multitude of medical and social complications.This study was conducted in a barangay in San Andres, Manila with the objective of determining the prevalence of alcohol intake among male adolescents and to describe the nature and strength of association of alcohol intake with self-esteem, self-efficacy, family function and respondents' belief that alcohol drinking is a group norm. A cross sectional research design was used. Six hundred thirty five (635) male adolescents, 12-18 years of age were selected using a simple random sampling.Simple analysis was done to estimate the prevalence of alcohol intake among male adolescents which was about 31(CI:27.14-34.46) Logistic regression analysis was used to determine the association of self-esteem, self-efficacy, family function and belief that alcohol drinking is a group norm and the respondents alcohol intake.The results of the logistic regression showed that low self-esteem was significantly associated with alcohol drinking among 12-13 years old first-borns (OR=11.88, CI 4.66-30.32) and middle-borns (OR=6, CI 1.14-31.18). Low self-esteem was not significantly associated with alcohol drinking among 12-13 years old, last born adolescents. The strength of association between low self-esteem and alcohol intake decreases with increasing birth order. This association at ages 14-15 years and 16-17 years was not significant. Moderate self-esteem appeared to be not assocaited with alcohol intake among the study subjects.The estimate of the association between low self-efficacy and alcohol intake although imprecise was strong and statistically significant (OR=16.85, CI 9.40-30.27).The strength of association between belief that alcohol drinking is a group norm and alcohol intake increased with birth order. The Magnitude of the PORs were higher for those who believe that, most if not all, of their peers drink alcohol (i.e., it is a group norm) than those who believe that only a few of their peers drink alcohol. The results showed that the last-borns who believe that few of their peers drink alcohol are almost ten times more likely to take alcohol than their counterparts who believe that none of their peers drink (OR=9.82, CI 1.55-62.28). The last-borns who believe that most or all of their peers drink alcohol are thirteen times more likely to take alcoholic bevarages than their counterparts who believe that their peers do not drink alcohol (OR=13.25, CI 2.26-77.73). The association between alcoghol intake and belief that alcohol drinking is a group norm appeared to be protective for the first borns who believe that few of their peers drink. However, this could easily be explained by chance. The association for the middle born adolescents was also not significant. This was also true for the first-borns and middle-borns who believe that alcohol intake is a group norm.This study, however, had no sufficient evidence to support a significant relationship between family function and alcohol intake.This study, however, had some limitations. Temporal ambiguity between exposure and outcome is an important issue since this study utilized a cross-sectional design.The instruments that were used to measure self-esteem, self-efficacy and family function were not validated for the local setting. No validation can be done to verify the truthfulness of the answers of the respondents with regard to both the exposure and outcome variable. The definition of drinkers includes a heterogenous mix of alcohol drinker.Enhancement of self-esteem and self-efficacy should be started early in sch